2018
DOI: 10.3847/1538-4357/aae82b
|View full text |Cite
|
Sign up to set email alerts
|

New Hot Subdwarf Stars Identified in Gaia DR2 with LAMOST DR5 Spectra

Abstract: We selected 4593 hot subdwarf candidates from the Gaia DR2 Hertzsprung-Russell (HR) diagram. By combining the sample with LAMOST DR5, we identified 294 hot subdwarf stars, including 169 sdB, 63 sdOB, 31 He-sdOB, 22 sdO, 7 He-sdO and 2 He-sdB stars. The atmospheric parameters (e.g., T eff , log g, log(nHe/nH)) are obtained by fitting the hydrogen (H) and helium (He) line profiles with synthetic spectra. Two distinct He sequences of hot subdwarf stars are clearly presented in the T efflog g diagram. We found tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 44 publications
12
57
0
1
Order By: Relevance
“…Figure 4 shows the comparisons of atmospheric parameters of 163 common stars between this study and Geier et al (2017), for which T eff , log g and log(y) are simultaneously available. As reported by Lei et al (2018), T eff and log(y) for both sample are quite similar. Although log g exhibits a larger dispersion than the former two parameters, our results agree with the values presented in the catalogue of Geier et al (2017).…”
Section: Spectral Analysissupporting
confidence: 76%
“…Figure 4 shows the comparisons of atmospheric parameters of 163 common stars between this study and Geier et al (2017), for which T eff , log g and log(y) are simultaneously available. As reported by Lei et al (2018), T eff and log(y) for both sample are quite similar. Although log g exhibits a larger dispersion than the former two parameters, our results agree with the values presented in the catalogue of Geier et al (2017).…”
Section: Spectral Analysissupporting
confidence: 76%
“…It means that we not only identified 241 new hot subdwarf stars, but also newly obtained atmospheric parameters for 255 hot subdwarf stars which were already cataloged in Geier et al (2017a). These results indicate the efficiency of our method to select hot subdwarf candidates by cross-matching these two large survey 4.8 5.0 5.2 5.4 5.6 5.8 6.0 6.2 6.4 6.6 6.8 logg(cm s 2 ) 5 4 3 2 1 0 1 2 3 4 log(nHe/nH) Hot subdwarfs in this study and Lei et al (2018) He-sdB n=9 He-sdO n=19 He-sdOB n=104 sdB n=355 sdO n=67 sdOB n=128 4.8 5.0 5.2 5.4 5.6 5.8 6.0 6.2 6.4 6.6 6.8 logg(cm s 2 )…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, we cross-matched all the 864 hot subdwarf sars identified in our series of studies with the Geier et al (2019) catalog, and found 833 common stars. This result demonstrate that nearly all the hot subdwarf stars identified in Lei et al (2018Lei et al ( , 2019b are included in Geier et al (2019) catalog. As described in section 2.3, 2513 candidates from the catalog of Geier et al (2019) have LAMOST spectra, of which 1348 have SNR-u larger than 10, and 833 of them were spectroscopically identified as hot subdwarf stars.…”
Section: Discussion and Summarymentioning
confidence: 55%
“…In our previous work, we have already identified 682 hot subdwarf stars by combining the Gaia DR2 database and the LAMOST DR5 database (Lei et al 2018(Lei et al , 2019b, among which 241 stars were newly discovered. In this study, we analyzed hot subdwarf candidates selected from the LAMOST DR6 and DR7 v0 database.…”
Section: Catalogue With Lamost Dr6 and Dr7mentioning
confidence: 99%
See 1 more Smart Citation